1996
DOI: 10.1136/thx.51.6.582
|View full text |Cite
|
Sign up to set email alerts
|

Effect of allergen avoidance at high altitude on direct and indirect bronchial hyperresponsiveness and markers of inflammation in children with allergic asthma.

Abstract: Background -Improvement of allergic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(85 citation statements)
references
References 10 publications
6
79
0
Order By: Relevance
“…The dissociation between methacholine and AMP responsiveness and markers of allergic inflammation has also been addressed in a recent study of allergen avoidance in children with allergic asthma [27]. The discrepancy may lie in the difference in their mechanisms of bronchoconstrictor effect, methacholine directly contracting airway smooth muscle and AMP releasing mast cell-derived mediators [8].…”
Section: Discussionmentioning
confidence: 99%
“…The dissociation between methacholine and AMP responsiveness and markers of allergic inflammation has also been addressed in a recent study of allergen avoidance in children with allergic asthma [27]. The discrepancy may lie in the difference in their mechanisms of bronchoconstrictor effect, methacholine directly contracting airway smooth muscle and AMP releasing mast cell-derived mediators [8].…”
Section: Discussionmentioning
confidence: 99%
“…There is convincing evidence that, in sensitized subjects with asthma [19,20] or allergic rhinitis [21,22], natural allergen exposure during a pollen season results in increased methacholine responsiveness. In addition, airway responsiveness to inhaled AMP increases during periods of natural allergen exposure in asthmatics [23]. but no information is available in subjects with allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 35 studies underwent further review. Critical review of complete texts of the 35 eligible studies identified two publications [9,10] that were excluded because they were based on data ultimately subsumed in two other publications [11,12]. We also found that a study set of one publication [13] was included within a larger cohort [14], so only the latter was included.…”
Section: Data Sources and Searchesmentioning
confidence: 98%
“…Weighted mean difference KOLESAR et al [19] BONER et al [20] BRIMKULOV (1) [22] BRIMKULOV (2) [22] PIACENTINI et al [23] SIMON et al [24] ALLEGRA et al [11] BONER et al (1) [25] BONER et al (2) [25] KOKOV [26] VAN VELZEN et al [12] VALLETTA et al [27] GROOTENDORST et al [28] PERONI et al [29] STRAUB et al [30] HUISMANS et al [ …”
mentioning
confidence: 99%